Wear-resistant and corrosion-resistant coating for pipeline and preparation method thereof
By using polyurethane resin, polytetrafluoroethylene, modified sepiolite and modified wear-resistant materials in the pipeline coating, combined with plasma technology, the existing coating is easily peeled off in a high sulfur-containing crude oil environment and The problem of insufficient corrosion resistance has achieved a significant improvement in the wear resistance and corrosion resistance of the coating.
Patent Information
- Application Number
- CN202411555771.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The existing pipeline coating is prone to peel off in a high sulfur-containing crude oil environment, and has insufficient corrosion resistance, resulting in premature scrapping of the pipeline.
Polyurethane resin and polytetrafluoroethylene are used as substrates, combined with modified sepiolite and modified wear-resistant materials, and silicon carbide is processed through plasma technology to form a stable network structure to improve the adhesion and wear resistance of the coating.
It significantly improves the wear resistance and corrosion resistance of the pipe coating, extends the service life of the coating, and reduces material waste.
Smart Images

Figure BDA0005116386110000091 
Figure BDA0005116386110000101
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating technology and relates to a wear-resistant and corrosion-resistant coating for pipelines and its preparation method. Background Technology
[0002] With the increasing amount of high-sulfur crude oil processed in my country's oil refining industry, the corrosion problem of pipelines caused by corrosive media such as sulfur, hydrogen sulfide, naphthenic acid, and sulfur dioxide in crude oil has become increasingly prominent. Pipelines for transporting crude oil, which are mainly made of carbon steel, are prematurely scrapped due to electrochemical corrosion and high-temperature corrosion, resulting in a large amount of material waste.
[0003] To solve the corrosion problem, coatings are often applied to the inner and outer walls of pipes. However, these coatings often have drawbacks such as low hardness, poor wear resistance, and short lifespan due to insufficient corrosion resistance.
[0004] Therefore, it is necessary to develop a coating for the inner wall of pipes with good wear resistance and excellent corrosion resistance to solve the problems of easy peeling and poor corrosion resistance of existing coatings and substrates. Summary of the Invention
[0005] The purpose of this invention is to provide a wear-resistant and corrosion-resistant coating for pipelines and a method for preparing the same, wherein the prepared coating for pipelines has excellent wear resistance and corrosion resistance.
[0006] The objective of this invention can be achieved through the following technical solutions:
[0007] A wear-resistant and corrosion-resistant coating for pipes comprises the following raw materials in parts by weight: 35-50 parts of polyurethane resin, 20-30 parts of polytetrafluoroethylene, 5-15 parts of modified sepiolite, 10-20 parts of modified wear-resistant material, 0.3-0.7 parts of defoamer, 1-3 parts of dispersant, 5-7 parts of curing agent and 70-80 parts of ethyl acetate;
[0008] The preparation process of the modified sepiolite is as follows:
[0009] Disperse 5-10 parts of sepiolite in 100 parts of a 1-3% potassium permanganate aqueous solution, then add 3-5 parts of manganese sulfate, stir at 130-160℃ for 4-8 hours, filter, wash with deionized water, and then dry at 95℃ for 8 hours to obtain manganese dioxide-modified sepiolite, which is the modified sepiolite.
[0010] As a preferred embodiment of the present invention, the preparation process of the modified wear-resistant material is as follows:
[0011] S1. First, crush silicon carbide, then keep the crushed silicon carbide powder at 1000-1200℃ for 1-1.5h, and cool it to room temperature to obtain pretreated silicon carbide nanoparticles.
[0012] S2. The pretreated silicon carbide nanopowder is washed with a 15% NaOH solution and deionized water, and dried to obtain solid powder A. Solid powder A is then processed by plasma technology to obtain solid powder B.
[0013] S3. Mix kaolin with sodium hydroxide solution at a mass ratio of 1:(4-5) evenly, then calcine at 180-230℃ for 8-12 hours, and cool to room temperature to obtain hydroxysappanite.
[0014] S4. Mix solid powder B, hydroxyl sodium arsenide and tetraethyl orthosilicate in an ethanol solution with a mass ratio of (1-1.5):1:(20-30). Adjust the pH of the solution to 11 with a 25% ammonia solution. Heat the solution to 40-70℃ and stir for 2-3 hours. After filtration, vacuum dry at 80-90℃ to obtain the modified wear-resistant material.
[0015] As a preferred embodiment of the present invention, the dispersant is one of polyacrylamide, polyethylene glycol monomethyl ether, and sodium lignosulfonate.
[0016] As a preferred embodiment of the present invention, the defoamer is one of polyoxypropylene glycerol ether and pentaerythritol stearate.
[0017] As a preferred embodiment of the present invention, the curing agent is one of hexamethylene diisocyanate and toluene diisocyanate.
[0018] As a preferred technical solution of the present invention, in step S52, during the plasma technology treatment, the gas introduced is air, the gas flow rate is 200-300 mL / min, the radio frequency power is 100-110 kW, and the treatment time is 220-300 s.
[0019] As a preferred embodiment of the present invention, in step S54, the mass-to-volume ratio of tetraethyl orthosilicate to ethanol solution in the tetraethyl orthosilicate ethanol solution is 1:30 g / mL.
[0020] A method for preparing a wear-resistant and corrosion-resistant coating for pipelines includes the following preparation process:
[0021] According to the weight proportions, polyurethane resin and polytetrafluoroethylene are dissolved in ethyl acetate and stirred at room temperature for 0.5 h. Modified sepiolite and modified wear-resistant material are then added and stirred for another 0.5 h. Defoamer, dispersant and curing agent are then added and ultrasonically stirred at 40-45℃ for 4-5 h to obtain a coating. The coating is then applied to the surface of the pipe and cured at 120-160℃ for 1-3 h to obtain the wear-resistant and corrosion-resistant coating for the pipe.
[0022] Sepiolite possesses excellent corrosion resistance. This mineral material can resist the erosion of various corrosive substances, including acids and alkalis. Its high corrosion resistance is mainly attributed to its high density, high heat resistance, and stable chemical composition. Manganese dioxide is loaded onto the surface of sepiolite using an in-situ growth method. As a hard material, manganese dioxide significantly improves the wear resistance of the coating and extends its service life. Furthermore, manganese dioxide has good chemical stability and corrosion resistance, resisting the erosion of various chemicals and protecting the substrate from corrosion. Introducing manganese dioxide particles increases the surface roughness of the coating, increasing the contact area between the coating and the substrate, which is beneficial for physical and mechanical bonding, thereby improving the adhesion between the coating and the pipe. This enhances the overall barrier and corrosion resistance of the coating, resulting in a long-term stable corrosion-resistant coating.
[0023] In this invention, hydroxysappanite is obtained by calcining kaolin mixed with alkali. The structure of hydroxysappanite consists of β-characteristic cages, which are connected in a specific way to form the unique framework structure of hydroxysappanite. This framework structure, together with other elements and groups, constitutes a stable mineral structure, thereby giving hydroxysappanite a certain degree of hardness.
[0024] Silicon carbide itself possesses excellent hardness and corrosion resistance. First, high-temperature calcination removes volatile components and unstable elements from the silicon carbide, thereby improving its purity. Simultaneously, sintering promotes particle bonding, forming a denser sintered body. Alkali treatment effectively removes impurities such as free silicon and silica from the silicon carbide surface, while also improving surface roughness and microstructure, potentially enhancing its chemical and thermal stability and extending its service life. Plasma treatment removes the oxide layer from the silicon carbide surface, improving its structure, increasing active sites, and enhancing surface smoothness, thus improving interfacial bonding and adhesion between silicon carbide and other polymers. Furthermore, plasma treatment introduces hydroxyl groups into the silicon carbide surface. Under alkaline conditions, tetraethyl orthosilicate acts as a crosslinking agent, combining with the hydroxyl groups on the silicon carbide surface and the abundant -OH groups on the hydroxyl sodalite surface to form a three-dimensional network structure. This network structure increases the structural stability of the coating, prevents peeling, and improves its wear resistance.
[0025] Both polytetrafluoroethylene (PTFE) and polyurethane (PU) have good corrosion resistance. By blending the two polymers as coating base materials, the chemical resistance of the material is further improved, and it remains stable in a wider range of chemical environments. At the same time, PTFE has excellent abrasion resistance, which helps to improve the overall abrasion resistance of the coating.
[0026] The beneficial effects of this invention are:
[0027] In this invention, polyurethane resin and polytetrafluoroethylene are used as the matrix materials for the coating. Modified sepiolite, prepared via an in-situ growth method, improves the interfacial compatibility between the modified sepiolite and the matrix, thereby enhancing the coating's corrosion resistance. A stable network structure is formed by the reaction of tetraethyl orthosilicate with the hydroxyl groups on the surface of hydroxyl-treated silicon carbide and sodalite, improving the coating's adhesion and wear resistance. The pipeline coating prepared by this invention exhibits excellent wear and corrosion resistance. Detailed Implementation
[0028] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.
[0029] Sepiolite: Purchased from Hubei Shixing Chemical Co., Ltd.;
[0030] Silicon carbide: purchased from Shanghai Jiadeer Chemical Technology Co., Ltd., item number: 144047;
[0031] Kaolin: Purchased from Jinan Shanhai Chemical Technology Co., Ltd.;
[0032] Tetraethyl orthosilicate: purchased from Shanghai Tangui New Materials Technology Co., Ltd.;
[0033] Polyurethane resin: purchased from Hubei Shixing Chemical Co., Ltd.;
[0034] Polytetrafluoroethylene: purchased from Beijing Zhisheng Weihua Chemical Co., Ltd.;
[0035] Polyoxypropylene glycerol ether: purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0036] Polyacrylamide: purchased from Shanghai Huichu Chemical Technology Co., Ltd.;
[0037] Hexamethylene diisocyanate: purchased from Shanghai Maclean Biochemical Technology Co., Ltd., product number: H811014;
[0038] In this invention, the mass-to-volume ratio of tetraethyl orthosilicate to ethanol in the ethanol solution is 1:30 g / mL.
[0039] Example 1
[0040] Preparation of modified sepiolite:
[0041] Five parts of sepiolite were dispersed in 100 parts of a 1% potassium permanganate aqueous solution, and then three parts of manganese sulfate were added. The mixture was stirred at 130°C for 4 hours. After stirring, the mixture was filtered, washed with deionized water, and then dried at 95°C for 8 hours to obtain manganese dioxide-modified sepiolite, which is the modified sepiolite.
[0042] Preparation of modified abrasion-resistant materials:
[0043] S1. First, crush silicon carbide, then keep the crushed silicon carbide powder at 1000℃ for 1 hour, and cool it to room temperature to obtain pretreated silicon carbide nanopowder.
[0044] S2. The pretreated silicon carbide nanopowder is washed with a 15% NaOH solution and deionized water, and dried to obtain solid powder A. Solid powder A is then treated with plasma technology to obtain solid powder B. During plasma technology treatment, the gas introduced is air, the gas flow rate is 200 mL / min, the radio frequency power is 100 kW, and the treatment time is 220 s.
[0045] S3. Kaolin with a mass ratio of 1:4 and sodium hydroxide solution with a concentration of 6 mol / L are mixed evenly, then calcined at 180℃ for 8 hours, and cooled to room temperature to obtain hydroxysappanite.
[0046] S4. Mix solid powder B, hydroxyl sodium arsenide and tetraethyl orthosilicate in an ethanol solution with a mass ratio of 1:1:20, adjust the pH of the solution to 11 with a 25% ammonia solution, heat to 40°C and stir for 2 hours, filter and vacuum dry at 80°C to obtain the modified wear-resistant material.
[0047] Preparation of wear-resistant and corrosion-resistant coatings for pipelines:
[0048] By weight, 35 parts of polyurethane resin and 20 parts of polytetrafluoroethylene were dissolved in 70 parts of ethyl acetate and stirred at room temperature for 0.5 h. Then, 5 parts of modified sepiolite and 10 parts of modified wear-resistant material were added and stirred for 0.5 h. Then, 0.3 parts of polyoxypropylene glycerol ether, 1 part of polyacrylamide and 5 parts of hexamethylene diisocyanate were added and ultrasonically stirred at 40 °C for 4 h to obtain a coating. The coating was applied to the surface of the pipe and cured at 120 °C for 1 h to obtain the wear-resistant and corrosion-resistant coating for the pipe.
[0049] Example 2
[0050] Preparation of modified sepiolite:
[0051] Eight parts of sepiolite were dispersed in 100 parts of a 2% potassium permanganate aqueous solution, and then four parts of manganese sulfate were added. The mixture was stirred at 140°C for 6 hours. After stirring, the mixture was filtered, washed with deionized water, and dried at 95°C for 8 hours to prepare manganese dioxide-modified sepiolite, which is the modified sepiolite.
[0052] Preparation of modified abrasion-resistant materials:
[0053] S1. First, crush silicon carbide, then keep the crushed silicon carbide powder at 1100℃ for 1.3h, and cool it to room temperature to obtain pretreated silicon carbide nanoparticles.
[0054] S2. The pretreated silicon carbide nanopowder is washed with a 15% NaOH solution and deionized water, and dried to obtain solid powder A. Solid powder A is then treated with plasma technology to obtain solid powder B. During plasma technology treatment, the gas introduced is air, the gas flow rate is 250 mL / min, the radio frequency power is 105 kW, and the treatment time is 260 s.
[0055] S3. Kaolin with a mass ratio of 1:4.5 is mixed evenly with a sodium hydroxide solution with a concentration of 7 mol / L, and then calcined at 200℃ for 10 h. After cooling to room temperature, hydroxysappanite is obtained.
[0056] S4. Mix solid powder B, hydroxyl sodium arsenide and tetraethyl orthosilicate in an ethanol solution with a mass ratio of 1.3:1:25. Adjust the pH of the solution to 11 with a 25% ammonia solution. Heat to 60°C and stir for 2.5 hours. After filtration and vacuum drying at 85°C, the modified wear-resistant material is obtained.
[0057] Preparation of wear-resistant and corrosion-resistant coatings for pipelines:
[0058] By weight, 40 parts of polyurethane resin and 25 parts of polytetrafluoroethylene were dissolved in 75 parts of ethyl acetate and stirred at room temperature for 0.5 h. Then, 10 parts of modified sepiolite and 15 parts of modified wear-resistant material were added and stirred for 0.5 h. Then, 0.5 parts of polyoxypropylene glycerol ether, 2 parts of polyacrylamide and 6 parts of hexamethylene diisocyanate were added and ultrasonically stirred at 44 °C for 4.5 h to obtain a coating. The coating was applied to the surface of the pipe and cured at 140 °C for 2 h to obtain the wear-resistant and corrosion-resistant coating for the pipe.
[0059] Example 3
[0060] Preparation of modified sepiolite:
[0061] Ten parts of sepiolite were dispersed in 100 parts of a 3% potassium permanganate aqueous solution, and then 5 parts of manganese sulfate were added. The mixture was stirred at 160°C for 8 hours. After stirring, the mixture was filtered, washed with deionized water, and dried at 95°C for 8 hours to prepare manganese dioxide-modified sepiolite, which is the modified sepiolite.
[0062] Preparation of modified abrasion-resistant materials:
[0063] S1. First, crush silicon carbide, then keep the crushed silicon carbide powder at 1200℃ for 1.5h, and cool it to room temperature to obtain pretreated silicon carbide nanoparticles.
[0064] S2. The pretreated silicon carbide nanopowder is washed with a 15% NaOH solution and deionized water, and dried to obtain solid powder A. Solid powder A is then treated with plasma technology to obtain solid powder B. During plasma technology treatment, the gas introduced is air, the gas flow rate is 300 mL / min, the radio frequency power is 110 kW, and the treatment time is 300 s.
[0065] S3. Mix kaolin with sodium hydroxide solution at a mass ratio of 1:5 and 8 mol / L until homogeneous. Then calcine at 230℃ for 8-12 hours and cool to room temperature to obtain hydroxysappanite.
[0066] S4. Mix solid powder B, hydroxyl sodium arsenide and tetraethyl orthosilicate in an ethanol solution with a mass ratio of 1.5:1:30, adjust the pH of the solution to 11 with a 25% ammonia solution, heat to 70°C and stir for 3 hours, filter and vacuum dry at 90°C to obtain the modified wear-resistant material.
[0067] Preparation of wear-resistant and corrosion-resistant coatings for pipelines:
[0068] By weight, 50 parts of polyurethane resin and 30 parts of polytetrafluoroethylene were dissolved in 80 parts of ethyl acetate and stirred at room temperature for 0.5 h. Then, 15 parts of modified sepiolite and 20 parts of modified wear-resistant material were added and stirred for 0.5 h. Then, 0.7 parts of polyoxypropylene glycerol ether, 3 parts of polyacrylamide and 7 parts of hexamethylene diisocyanate were added and ultrasonically stirred at 45 °C for 5 h to obtain a coating. The coating was applied to the surface of the pipe and cured at 160 °C for 3 h to obtain the wear-resistant and corrosion-resistant coating for the pipe.
[0069] Comparative Example 1
[0070] The difference between Comparative Example 1 and Example 1 is that the sepiolite in Comparative Example 1 was not modified in any way, while the other operations were the same.
[0071] Comparative Example 2
[0072] The difference between Comparative Example 2 and Example 1 is that the modified wear-resistant material in Comparative Example 2 was not treated with tetraethyl orthosilicate, while the other operations were the same.
[0073] Comparative Example 3
[0074] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, silicon carbide and hydroxyl sodium sappanite were not modified in any way during the preparation of the modified wear-resistant material. That is, silicon carbide and hydroxyl sodium sappanite were mixed to obtain the wear-resistant material. All other operations were the same.
[0075] Performance testing:
[0076] 1. Abrasion resistance test:
[0077] Adhesion test: according to GB / T 9286-1998;
[0078] Hardness: The hardness of the obtained coating was tested according to GB / T 6739-2022 "Determination of Hardness of Paints and Varnishes by Pencil Method". The pencil brand used was Zhonghua.
[0079] Abrasion resistance: The abrasion resistance of this invention was measured using a JM IV abrasion tester and the rotating friction rubber wheel method. The average value of the coating mass loss (weight loss method) after 100 grinding revolutions was used to measure the abrasion resistance. The applied load was 10N, the rotation speed was 80r / min, the test temperature was 25℃, and the relative humidity was 50%. The mass was measured to an accuracy of 0.01mg, and the average value of three measurements was taken as the result. The results are shown in Table 1 below:
[0080] Table 1
[0081] Group Adhesion / Grade hardness Wear amount / mg Example 1 0 7H 10.23 Example 2 0 7H 9.98 Example 3 0 6H 10.74 Comparative Example 2 1 3H 18.69 Comparative Example 3 3 H 30.03
[0082] 2. Corrosion resistance test:
[0083] According to GB / T 1771-2007 Test of Neutral Salt Spray Resistance of Paints and Varnishes, the acid resistance was tested by immersing the coating in a 10% sulfuric acid solution for 720 hours. The alkali resistance was tested by immersing the coating in a 10% sodium hydroxide solution for 720 hours. The test results are shown in Table 2 below.
[0084] Table 2
[0085]
[0086]
[0087] Based on the above data, it can be seen that the coating prepared by the present invention has excellent corrosion resistance and wear resistance.
[0088] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as above in terms of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art can, without departing from the scope of the technical solution of the present invention, make some changes or modifications to equivalent embodiments using the technical contents disclosed above. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A wear-resistant and corrosion-resistant coating for a pipeline, characterized in that: The invention comprises the following raw materials in parts by weight: 35 to 50 parts of polyurethane resin, 20 to 30 parts of polytetrafluoroethylene, 5 to 15 parts of modified sepiolite, 10 to 20 parts of modified wear-resistant material, 0.3 to 0.7 parts of defoaming agent, 1 to 3 parts of dispersant, 5 to 7 parts of curing agent and 70 to 80 parts of ethyl acetate; The preparation process of the modified sepiolite is as follows: Disperse 5 to 10 parts of sepiolite in 100 parts of a potassium permanganate aqueous solution with a mass fraction of 1 to 3%, add 3 to 5 parts of manganese sulfate, and stir at 130 to 160° C. for 4 to 8 hours. After stirring, filter, wash with deionized water, and dry at 95° C. for 8 hours to obtain sepiolite in situ modified with manganese dioxide, that is, the modified sepiolite.
2. The wear-resistant and corrosion-resistant coating for pipelines according to claim 1, characterized in that: The preparation process of the modified wear-resistant material is as follows: S1, crushing the silicon carbide first, then keeping the crushed silicon carbide powder at 1000-1200° C. for 1-1.5 hours, and cooling to room temperature to obtain pretreated silicon carbide nanopowder; S2, washing the pretreated silicon carbide nanopowder with a 15% by mass NaOH solution and deionized water, and obtaining solid powder A after drying, and treating solid powder A by plasma technology to obtain solid powder B; S3, mixing kaolin with a mass ratio of 1: (4-5) and a sodium hydroxide solution with a concentration of 6-8 mol / L, and then calcining at 180-230° C. for 8-12 h, and cooling to room temperature to obtain hydroxysodalite; S4. Mix solid powder B, hydroxysodalite and ethanol solution of tetraethyl orthosilicate in a mass ratio of (1-1.5):1:(20-30), adjust the pH value of the solution to 11 with 25% ammonia aqueous solution, heat to 40-70°C and stir for 2-3h, filter and vacuum dry at 80-90°C to obtain modified wear-resistant material.
3. The wear-resistant and corrosion-resistant coating for pipelines according to claim 1, characterized in that: The dispersant is one of polyacrylamide, polyethylene glycol monomethyl ether and sodium lignin sulfonate.
4. The wear-resistant and corrosion-resistant coating for pipelines according to claim 1, characterized in that: The defoaming agent is one of polyoxypropylene glyceryl ether and pentaerythritol stearate.
5. The wear-resistant and corrosion-resistant coating for pipeline according to claim 1, characterized in that: The curing agent is one of hexamethylene diisocyanate and toluene diisocyanate.
6. The wear-resistant and corrosion-resistant coating for pipeline according to claim 1, characterized in that: In step S52, during the plasma treatment, the gas introduced is air, the gas flow rate is 200-300 mL / min, the radio frequency power source power is 100-110 kW, and the treatment time is 220-300 s.
7. The wear-resistant and corrosion-resistant coating for pipeline according to claim 1, characterized in that: In step S54, the mass volume ratio of tetraethyl orthosilicate to the ethanol solution in the ethanol solution of tetraethyl orthosilicate is 1:30 g / mL.
8. A method for preparing a wear-resistant and corrosion-resistant coating for a pipeline according to any one of claims 1 to 7, characterized in that: The preparation process includes the following: Dissolve polyurethane resin and polytetrafluoroethylene in ethyl acetate by weight, stir at room temperature for 0.5 h, continue to add modified sepiolite and modified wear-resistant material and stir for 0.5 h, then add defoamer, dispersant and curing agent, and stir ultrasonically at 40-45° C. for 4-5 h to obtain a coating; The coating is applied on the surface of the pipeline and cured at 120-160° C. for 1-3 hours to obtain the wear-resistant and corrosion-resistant coating for the pipeline.
Citation Information
Patent Citations
Method for preparing micro spherical niobium (Nb)-wolfram (W)-molybdenum (Mo)-zirconium (Zr) alloy powder
CN103121105A
Anticorrosive polyethylene communication pipe and preparation method thereof
CN110256753A
Modification method of electromagnetic shielding aging-resistant glass coating liquid
CN110746879A
Preparation method of impact-resistant glass based on plasma treatment
CN111515101A
Silicon-carbon composite material as well as preparation method and application thereof
CN117976881A
Cited By
Corrosion-resistant thermal insulation composite material and preparation method thereof
CN119823560A